Left interval thoracoscopic pneumonectomy for type II communicating bronchopulmonary foregut malformation in a 17-month-old girl. (2020) - Miyano, Go; Watanabe, Yukio; Hayashi, Takuo; Lane, Geoffrey J.; Suzuki, Kenji; Yamataka, Atsuyuki
Highlights: Type II CBPFM: no main bronchus and underdeveloped lung connected to the oesophagus. No incidence is reported but there are less than 30 cases in the English literature. Typical presentation of CBPFM is by 2 years old with chronic cough and pneumonia. CBPFM was approached dorsally; all trocars were placed along the erector spinae. Intensive conservative management contributed to successful thoracoscopic surgery. Abstract: Introduction: Communicating bronchopulmonary foregut malformation (CBPFM) is a rare congenital anomaly comprising a spectrum of airway anomalies connected to the oesophagus or stomach. Our management of a case of CBPFM is presented to improve knowledge of its treatment. Presentation of case: A 17-month-old Japanese girl presented with fever (39.1 °C) and persistent cough. She was noted to be poorly developed (7.5 kg: −2SD). Chest X-ray radiography was suggestive of pneumonia involving the left lung; WBC was 41600/μL and CRP was 12.9 mg/dL. Computed tomography, upper gastrointestinal series, and bronchoscopy identified a fistula between the oesophagus and the left lung and severe left pulmonary artery hypoplasia, typical of type II CBPFM. Her left thoracic cavity was small with sclerotic lung tissue. We customised management by commencing a trial of intensive duodenal tube feeding without oral ingestion. She gained weight and her pneumonia improved enough to enable thoracoscopic left pneumonectomy through an unconventional dorsal approach, necessary because of the location of her CBPFM. Surgery was successful and tolerated well with unremarkable postoperative recovery. Currently she is asymptomatic and growing well. Discussion: We used minimally invasive surgery (MIS) to resect an anomalous bronchus and perform a left pneumonectomy after two weeks of intensive conservative management, including nil-by-mouth to optimise her condition for surgery. Conclusion: Our case provides further evidence that CBPFM can be treated successfully by MIS (interval thoracoscopic pneumonectomy), especially after a period of intensive conservative management. Interval surgery should be considered actively prior to major surgery in smaller children if indicated.